Quality of service and user satisfaction of a police station in a district of northern Lima - Vilca Malaver, Yanko Yoshitaro; Meneses Claudio, Brian Andreé; Zapana Ruiz, Jorge Arturo (Southern perspective / Perspectiva austral, 2024)
The situation about the attention people receive in the police stations of our country is poor, many users go to these waiting to be attended by police officers after some event or other need, but what they receive is an unfair and degrading treatment, which is why the research seeks to determine the relationship between the quality of service and the user satisfaction of a police station in a district of Lima Norte, 2023. The type of the research is basic, correlative research, cross-sectional, which is applied to a sample of 81 users who are studied through a survey, having as results that talking about quality of service a 43,2 % of the respondents said it was low, a 39,5 % considered it medium and only a 17,3 % considered it high, while regarding user satisfaction, the 53,1 % of the respondents considered it low, a 30,9 % considered it medium and only 16% considered it high, then the Rho Spearman coefficient is applied to establish the correlation, having as result a degree of significance of 0,001, so the existence of a relationship between quality service and user satisfacción is corroborated, also a coefficient of 0,814 is obtained, which indicates a direct and high correlation between the variables, this is because if users receive a bad attention by the police in the police station, the user satisfaction about the service will be equally bad